A Generalization of the Composite-Good Theorem for Imperfect Markets - Livitan, Nissan (Review of Economic Studies, 1966)
Journal Article A Generalization of the Composite-Good Theorem for Imperfect Markets Get access Nissan Liviatan Nissan Liviatan The Hebrew University of Jerusalem Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 33, Issue 1, January 1966, Pages 45–56, https://doi.org/10.2307/2296640 Published: 01 January 1966